2013
DOI: 10.1002/j.2333-8504.2013.tb02337.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Reading Literacy Assessment Framework: Foundation and Rationale for Assessment and System Design

Abstract: Since its 1947 founding, ETS has conducted and disseminated scientific research to support its products and services, and to advance the measurement and education fields. In keeping with these goals, ETS is committed to making its research freely available to the professional community and to the general public. Published accounts of ETS research, including papers in the ETS Research Report series, undergo a formal peer-review process by ETS staff to ensure that they meet established scientific and professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 96 publications
1
40
0
Order By: Relevance
“…For example, Educational Testing Service (ETS) has developed an innovative suite of computer-delivered assessments called the Global Integrated Scenario-based Assessments (GISA). GISA is a theoretically based measure designed to reflect an updated understanding of the construct of reading comprehension while taking advantage of the affordances of technological delivery Sabatini, O'Reilly, & Deane, 2013). In the study reported here, we use the GISA as our outcome measure of deep reading comprehension (see Methods section for a fuller description of the test and its psychometric properties).…”
Section: Deep Reading Comprehensionmentioning
confidence: 99%
“…For example, Educational Testing Service (ETS) has developed an innovative suite of computer-delivered assessments called the Global Integrated Scenario-based Assessments (GISA). GISA is a theoretically based measure designed to reflect an updated understanding of the construct of reading comprehension while taking advantage of the affordances of technological delivery Sabatini, O'Reilly, & Deane, 2013). In the study reported here, we use the GISA as our outcome measure of deep reading comprehension (see Methods section for a fuller description of the test and its psychometric properties).…”
Section: Deep Reading Comprehensionmentioning
confidence: 99%
“…The second installment of the reading framework built upon the first by providing a definition of reading for understanding, the key constructs to be assessed, a position on reading development, and an overview of two types of assessments (Sabatini, O'Reilly, & Deane, 2013).…”
Section: Background and Context: The Two Prior Frameworkmentioning
confidence: 99%
“…For example, Reed and Santi ( 2015 ) note that common recommendations for addressing the needs of LD students include: explicit vocabulary instruction in content area texts; supplementing student's background knowledge of relevant concepts; providing instruction in making inferences in relating ideas in a text; and improving students' metacognitive strategies by answering questions, paraphrasing, or writing summaries. These are all explicit features included in the next generation of assessments we have been describing Sabatini et al, 2013 ;Sabatini, O'Reilly, Halderman, & Bruce, 2014 ).…”
Section: Implications For Students With Learning Disabilitiesmentioning
confidence: 98%
“…Students are expected to integrate, synthesize (Goldman, 2012 ), and evaluate (Metzger, 2007 ) multiple sources of information (Britt & Rouet, 2012 ) to satisfy their specifi c purposes and goals for reading. Increasingly, students are encouraged to collaborate and communicate with one another (NGA & CCSSO, 2010 ) as they solve problems and make decisions (Sabatini, O'Reilly, & Deane, 2013 ), often in digital environments (Coiro, 2011 ). Collectively, these new standards, expectations and arguments for updating the construct of reading will undoubtedly impact future test scoreseducators could potentially be faced with new skill gaps.…”
Section: Background and Contextmentioning
confidence: 99%